Method for preparing roadbed and pavement building materials from construction solid waste polymers

By using barium hydroxide as an exciter for high-pressure activation during the activation of construction solid waste and adding compensator to adjust chemical composition, the problem of unsatisfactory polymerization reaction during the activation of construction solid waste is solved, and efficient utilization of construction solid waste is achieved to prepare geopolymer gelling materials with excellent mechanical properties.

CN116751002BActive Publication Date: 2025-04-15XIAN RES & DESIGN INST OF WALL & ROOF MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310833907.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-04-15
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize construction solid waste, especially during the activation process, the proportions of silicon, aluminum, and alkali and reaction conditions are difficult to be appropriate, resulting in unsatisfactory polymerization reaction and the inability to obtain excellent geopolymer gelling materials.

Method used

Barium hydroxide is used as the main exciter for high pressure activation to promote the dissolution efficiency of activated silicon and aluminum, and a compensator is added to adjust the proportion and pH of silicon, aluminum, and alkali to form a gelled material with a mass-tight three-dimensional network structure with sodium and calcium as the center cation.

Benefits of technology

The full utilization of construction solid waste is achieved, the cost of raw materials is reduced, the preparation efficiency is improved, and the secondary energy consumption is avoided. The prepared construction solid waste base polymer gelling material has high early strength, fast settling time, good durability and corrosion resistance, and is suitable for building materials for roadbeds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116751002B_ABST
    Figure CN116751002B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a roadbed and pavement building material from a construction solid waste-based polymer. The construction solid waste-based polymer gelling material prepared from construction solid waste as raw materials and construction waste-based regenerated sand are mixed with aggregate and water through batching, stirring, molding and curing to prepare the roadbed and pavement building material. The invention adopts barium hydroxide as the main activator and activates it under high pressure to promote the dissolution efficiency of active silicon and aluminum in the construction solid waste, and combines the addition of a compensating agent to promote polymerization to obtain a construction solid waste-based polymer gelling material with a dense three-dimensional network structure. The gelling material has the characteristics of early strength and fast hardening, durable corrosion resistance and freeze-thaw resistance, and has stable mechanical properties and strong ability to fix toxic metal ions, and is suitable for roadbed and pavement building materials. At the same time, the invention also obtains construction waste-based regenerated sand, and the two are used to prepare roadbed and pavement building materials, thereby achieving full utilization of construction solid waste and improving preparation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization of construction solid waste, and specifically relates to a method for preparing building materials for roadbed and pavement from construction solid waste base polymers. Background Art

[0002] Geopolymer (also known as inorganic polymer, referred to as geopolymer) is an amorphous gelling material with a three-dimensional network structure composed of silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron. Geopolymer materials have received extensive attention in the past few decades due to their excellent mechanical properties, chemical stability and high temperature resistance.

[0003] Geopolymers are usually made of active silicon-aluminum materials as the main raw materials, and are prepared by stirring, mixing, molding and curing under the action of alkaline activators. They are formed through a series of complex reactions: dissolution of silicon-aluminum raw materials, depolymerization of aluminum-oxygen tetrahedrons and silicon-oxygen tetrahedrons, and re-condensation of aluminum-oxygen tetrahedrons and silicon-oxygen tetrahedrons to form a three-dimensional network structure of gelling materials. Among them, the performance of the metakaolin-sodium silicate / sodium hydroxide system is the best.

[0004] Usually, active alumina-silica materials are made of metakaolin, which is mainly prepared by lightly burned kaolin; the alkaline activators are mainly water glass and sodium hydroxide. The geopolymer products of this system have excellent performance and good mechanical and durability indicators. However, metakaolin is still an industrial waste activation process. Compared with the production process of sodium silicate, the two are two parallel routes in the preparation process of geopolymer, which means that energy consumption is required twice. If these two processes can be integrated and unified, the application threshold of geopolymer will be greatly reduced.

[0005] At present, many scholars are looking for substitutes for metakaolin, such as fly ash, slag, red mud, slag and other industrial wastes, which have been activated and used in geopolymers, and have achieved breakthroughs to varying degrees. However, the dependence on sodium silicate is still unresolved.

[0006] In the previous research on construction solid waste (construction waste and shield soil), the applicant found that muscovite, phlogopite and montmorillonite have properties similar to kaolin after treatment and can be used for the preparation of geopolymers. However, the difficulty lies in the fact that the composition of these construction solid wastes (construction waste and shield soil) is relatively complex. In the analysis of the composition of construction solid waste in some areas, it was found that the total content of kaolinite, muscovite, phlogopite and montmorillonite in its composition is 20% to 40%, but the content of quartz sand and gravel is also 40% to 60%. If the light burning process is used, it is not rational to activate quartz unless the enrichment of potential active materials is completed in advance. In addition, the light burning process is not rational for the activation performance of materials with complex mineral compositions.

[0007] The ideal technical route is to activate both types of minerals in construction waste (construction waste and shield soil) through an activation method; then add auxiliary conditioning agents and stir to directly prepare geopolymer cementitious materials. The difficulty lies in the ratio of silicon, aluminum and alkali and the reaction conditions during the activation process. If the ratio is not appropriate, polymerization will occur during the activation process, and the ideal geopolymer cementitious material cannot be obtained. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a method for preparing roadbed and pavement building materials from construction solid waste-based polymers in view of the deficiencies of the above-mentioned prior art. The method uses construction solid waste as raw materials, adopts barium hydroxide as the main activator and performs a high-pressure activation to promote the dissolution efficiency of active silicon and aluminum, combines the addition of a compensating agent to promote polymerization, obtains a gelling material with a dense three-dimensional network structure with sodium and calcium as central cations, and simultaneously obtains construction waste-based regenerated sand, and both are used to prepare roadbed and pavement building materials, thereby achieving full utilization of construction solid waste and solving the problem of difficulty in activating existing construction solid waste.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing building materials for roadbed and pavement from construction solid waste-based polymers, characterized in that construction solid waste-based polymer cementitious materials prepared with construction solid waste as raw materials and construction waste-based regenerated sand and aggregate, water are batched, stirred, formed, and cured to prepare building materials for roadbed and pavement; the building materials for roadbed and pavement include high-strength sleepers, imitation stone bricks for roads, and permeable bricks for roads.

[0010] The above-mentioned method for preparing building materials for roadbed and pavement from construction solid waste-based polymers is characterized in that the raw materials for preparing the construction solid waste-based polymer cementitious materials and the construction waste-based regenerated sand are derived from shield soil or construction waste in construction solid waste, and the mineral components in the preparation raw materials contain muscovite, phlogopite, montmorillonite and quartz with a total mass content greater than 60%, and the mass content of SiO2 in the chemical composition of the preparation raw materials is greater than 50%, and the mass content of Al2O3 is not less than 15%.

[0011] The above-mentioned method for preparing a roadbed and pavement building material from a construction solid waste base polymer is characterized in that the construction solid waste base polymer gelling material is made by proportioning, mixing and stirring an active slurry and a compensating agent, and the soluble activator added to the active slurry is barium hydroxide and hydrogen peroxide, or barium hydroxide, hydrogen peroxide and sodium hydroxide, and the compensating agent contains sodium, calcium and aluminum ions, wherein the preparation method of the active slurry comprises the following steps:

[0012] Step 1: Raw material screening: The raw material construction solid waste is passed through a 1mm aperture sieve to obtain undersize material and oversize material, and the oversize material is used for construction waste-based regenerated sand;

[0013] Step 2, stirring: adding a soluble stimulant into water, stirring evenly and then standing for more than 2 hours to obtain a pre-addition solution with a concentration of 200 g / L, then mixing the undersize obtained in step 1 with the pre-addition solution and stirring with a high-speed disperser to obtain a preliminary slurry; the stirring speed is 3000 rpm and the stirring time is 20 minutes;

[0014] Step 3, high-pressure activation: placing the prepared slurry obtained in step 2 in a reaction kettle for high-pressure activation to obtain an activated mixed slurry; the temperature of the high-pressure activation is 120°C to 150°C, the pressure is 0.2MPa to 0.5MPa, and the pressure holding time is 2h;

[0015] Step 4: Slurry-sand separation: The activated mixed slurry obtained in step 3 is passed through a 180-mesh sieve to obtain the slurry below the sieve, i.e., the active slurry, and the residue above the sieve, which is used as construction waste-based regenerated sand.

[0016] Silicate clay minerals and quartz will dissolve under alkaline conditions and then polymerize with central cations to form a three-dimensional network structure. The present invention has found that potassium, sodium and calcium are the best central cations from the perspective of the product, and the mechanical properties of their products are relatively excellent. Among them, calcium hydroxide is a poorly soluble substance, so it cannot be used, while sodium has the strongest ability to combine with silicon and aluminum, and its hydroxide is easily soluble in water, so it is better to use.

[0017] At the same time, general geopolymers use metakaolin as raw material, sodium silicate and sodium hydroxide as activators, and the actual role of sodium silicate is to provide more active silicon (compared with metakaolin) to induce polymerization. Metakaolin is formed by thermal activation, in a non-alkaline environment, and has no central cations; sodium silicate solution is alkaline, without active aluminum and central cations. Therefore, sodium hydroxide is used as a base to activate the substance containing silicon and aluminum at the same time, and the polymerization reaction occurs in the activation stage.

[0018] Based on the above research results, the present invention adopts soluble alkali barium hydroxide as the main activator. Since the binding ability of barium to active silicon and aluminum is weak, the stability of the three-dimensional network structure material generated after the polymerization reaction is poor, that is, most of the active silicon and aluminum and the central cation are not polymerized, or the degree of polymerization is very low. At the same time, a hydrogen peroxide inhibitor that can provide alkalinity is used, or sodium hydroxide is added as an auxiliary activator, and the polymerization reaction is inhibited by adjusting the pH value. The high-pressure activation is combined to increase the dissolution efficiency of the active silicon and aluminum, thereby realizing the simultaneous activation of silicon and aluminum in an alkaline environment to obtain an active slurry.

[0019] At the same time, the present invention adds a compensating agent containing sodium, calcium and aluminum ions into the active slurry, and adds water to adjust the appropriate pH value to complete polymerization to generate a gelling material with a dense three-dimensional network structure with sodium and calcium as central cations.

[0020] The above-mentioned method for preparing building materials for roadbed and pavement from construction solid waste base polymers is characterized in that the compensating agent is prepared from one or more of gasified slag, fly ash and slag, and the mass content of Al2O3 in the compensating agent is greater than 15%, the mass content of CaO is greater than 10%, the mass content of Na2O is greater than 3%, and the grading is less than 180 mesh.

[0021] Since the content of clay minerals in most raw materials of construction solid waste is not high, the performance after activation is general. The compensating agent of the above composition used in the present invention is active itself and can be used as the main material of geopolymer. The most important thing is to supplement the performance of active silicon-aluminum reinforced products, and by introducing calcium and sodium to replace the unstable barium in the active slurry, a more dense and stable petrochemical body is generated, thereby improving the quality of the construction solid waste geopolymer cementitious material. In addition, the compensating agent of the present invention only needs to provide a certain amount of sodium, calcium, and aluminum, so it comes from gasification slag, fly ash and slag, realizing the utilization of industrial waste slag and reducing the cost of raw materials.

[0022] The above-mentioned method for preparing a roadbed and pavement building material from a polymer based on construction solid waste is characterized in that the method for preparing a construction solid waste based polymer cementitious material by proportioning, mixing and stirring the active slurry and the compensating agent comprises the following steps:

[0023] Step 1: According to the design requirements of the polymer cementitious material based on construction solid waste, the amount of active slurry and compensating agent are calculated respectively, and the mass ratio of active slurry to compensating agent is 1.1-1.4:1;

[0024] Step 2. Weigh the active slurry according to the calculated amount in step 1, and pre-stir it for 30 seconds using a disperser, then add a compensating agent and continue stirring for 10 minutes to prepare a construction solid waste base polymer cementitious material; the construction solid waste base polymer cementitious material is used to prepare roadbed and pavement building materials within 3 minutes after preparation, otherwise the construction solid waste base polymer cementitious material must be stirred again at a speed of 1800 rpm for 5 minutes before being used to prepare roadbed and pavement building materials.

[0025] In the proportioning process of the present invention, the amounts of active slurry and compensating agent are usually proportioned according to the design requirements of the construction solid waste base polymer cementitious material, and the ratio among silicon, aluminum and alkali in the active slurry is adjusted by the compensating agent to adjust the speed and degree of the polymerization reaction for preparing the construction solid waste base polymer cementitious material, and control the strength and other properties of the construction solid waste base polymer cementitious material.

[0026] In addition, the present invention strictly limits the time from the preparation of the construction solid waste-based polymer gelling material to the application process to ensure its performance.

[0027] The above-mentioned method for preparing a roadbed and pavement building material from a construction solid waste base polymer is characterized in that the mass ratio of the aggregate to the construction solid waste base polymer cementitious material is 1.9 to 2.3:1;

[0028] When the roadbed and pavement construction material is a high-strength rail sleeper, the gravel in the aggregate is a natural stone gradation composed of particle sizes of 5mm-10mm and 10mm-20mm in a mass ratio of 3:7, the sand-gravel ratio is 0.5, and the supplementer used in preparing the construction solid waste base polymer cementitious material is fly ash;

[0029] When the roadbed and pavement construction material is imitation stone bricks for roads, the gravel in the aggregate is a natural stone gradation with a particle size of 3 mm to 5 mm, the sand-gravel ratio is 0.8, the supplementer used in preparing the construction solid waste base polymer cementitious material is gasified slag, and the maintenance system for preparing the imitation stone bricks for roads is natural maintenance;

[0030] When the construction material for the roadbed and pavement is permeable road bricks, the gravel in the aggregate is a natural stone grading with a particle size of 8mm to 15mm, the sand-gravel ratio is 0.4, the supplementer used to prepare the construction solid waste base polymer cementitious material is slag, and the maintenance system for preparing permeable road bricks is natural maintenance.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1. The present invention prepares construction materials for roadbed and pavement by mixing, stirring, molding and curing construction solid waste-based polymer cementitious materials and construction waste-based regenerated sand, aggregate and water, thereby making full use of construction solid waste and avoiding waste of resources.

[0033] 2. The present invention uses construction solid waste as raw material, adopts barium hydroxide as the main activator and performs a high-pressure activation to promote the dissolution efficiency of active silicon and aluminum, and combines the addition of a compensating agent to complete polymerization to obtain a gelling material with a dense three-dimensional network structure with sodium and calcium as central cations. It realizes the preparation of construction solid waste-based polymer gelling materials with construction solid waste raw materials, and obtains construction waste-based regenerated sand during activation, thereby improving the preparation efficiency and avoiding secondary energy consumption.

[0034] 3. The present invention uses compensating agents derived from wastes such as gasified slag, fly ash and slag to participate in the preparation of construction solid waste base polymer cementitious materials, thereby realizing the utilization of industrial waste slag and reducing raw material costs.

[0035] 4. The present invention uses construction solid waste as raw materials to prepare construction solid waste-based polymer cementitious materials and construction waste-based regenerated sand, and the preparation process does not rely on non-renewable limestone resources, thereby reducing resource consumption and is a green building material.

[0036] 5. The construction solid waste base polymer cementitious material prepared by the present invention has the characteristics of high early strength, fast setting time, early strength and fast hardening, and good mechanical properties; at the same time, no sulfoaluminate minerals such as calcium sulfonate are produced during hydration, so it is resistant to sulfate corrosion, and shows good stability in acidic solutions and various organic solvents, has excellent durability and corrosion resistance, and is suitable for construction materials for roadbeds and pavements.

[0037] 6. The construction solid waste base polymer cementitious material prepared by the present invention can form a dense structure with high strength and excellent anti-seepage performance, and the electrolyte concentration in the pore solution is relatively high, so the ability to resist freeze-thaw cycles is enhanced, and it is particularly suitable for construction materials for roadbeds and pavements under extreme temperature conditions.

[0038] 7. The basic structure of the construction solid waste base polymer cementitious material prepared by the present invention is a three-dimensional network of zeolite-like cage structures composed of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons. This special structure can effectively solidify heavy metals in the form of chemical bonds and physical adsorption, and has a strong ability to fix toxic metal ions. The fixation rate of Hg, As, Fe, Mn, Ar, Co, and Pb is more than 90%, and the "cage-type" network skeleton is still relatively stable even under the action of nuclear radiation. It is suitable for construction materials for roadbeds and pavements in heavy metal contaminated or even nuclear radiation areas.

[0039] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0040] Attached photos

[0041] Figure 1 The present invention is a process flow chart for preparing construction materials for roadbed and pavement from construction solid waste base polymers. DETAILED DESCRIPTION

[0042] The construction solid waste used in Examples 1 to 3 of the present invention comes from subway shield soil and construction waste in a certain place in Guangzhou, and the compensating agent raw materials come from gasified slag, fly ash and slag in a certain place in Inner Mongolia. The corresponding chemical and mineral component mass contents are shown in Tables 1 to 7.

[0043] Table 1 Chemical composition of subway shield soil

[0044] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> <![CDATA[TiO2]]> Loss on ignition content(%) 59.68 22.05 2.11 0.26 0.54 2.25 0.40 0.41 1.05 11.10

[0045] Table 2 Mineral composition of subway shield soil

[0046] Mineral composition quartz Phlogopite muscovite Chlorite Montmorillonite other content(%) 17 20 28 16 - 19

[0047] Table 3 Chemical composition of construction waste

[0048] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> <![CDATA[TiO2]]> Loss on ignition content(%) 50.75 21.59 10.64 0.24 0.59 2.54 1.23 0.41 0.68 10.11

[0049] Table 4 Mineral composition of construction waste

[0050] Mineral composition quartz Phlogopite muscovite Chlorite Montmorillonite other content(%) 45 16 11 22 4 15

[0051] Table 5 Chemical composition of gasified slag

[0052]

[0053]

[0054] Table 6 Chemical composition of fly ash

[0055] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> <![CDATA[TiO2]]> Loss on ignition content(%) 50.84 15.27 4.33 15.08 1.11 1.31 1.29 3.68 0.93 1.83

[0056] Table 7 Chemical composition of slag

[0057] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> <![CDATA[TiO2]]> Loss on ignition content(%) 56.19 15.37 2.99 14.73 1.14 1 2.82 0.26 0.75 0.52

[0058] Example 1

[0059] like Figure 1 As shown, in this embodiment, subway shield soil and construction waste soil in a mass ratio of 1:1 are used as construction solid waste raw materials to prepare construction solid waste-based polymer cementitious materials and construction waste-based regenerated sand, which are then mixed with aggregate and water through batching, mixing, molding, and curing to prepare high-strength rail sleepers;

[0060] The process for preparing the active slurry in the construction solid waste-based polymer cementitious material comprises the following steps:

[0061] Step 1: Raw material screening: The raw material construction solid waste is passed through a 1mm aperture sieve to obtain undersize material and oversize material, and the oversize material is used for construction waste-based regenerated sand;

[0062] Step 2, stirring: adding barium hydroxide in a mass ratio of 4:1 and hydrogen peroxide with a mass concentration of 6% as a soluble stimulant into water, stirring evenly and standing for more than 2 hours to obtain a pre-addition solution with a concentration of 200 g / L, and then mixing the undersize obtained in step 1 with the pre-addition solution and stirring with a high-speed disperser to obtain a preliminary slurry; the stirring speed is 3000 rpm, and the stirring time is 20 minutes;

[0063] Step 3, high-pressure activation: placing the prepared slurry obtained in step 2 in a reaction kettle for high-pressure activation to obtain an activated mixed slurry; the temperature of the high-pressure activation is 120° C., the pressure is 0.2 MPa, and the pressure holding time is 2 h;

[0064] Step 4, slurry-sand separation: the activated mixed slurry obtained in step 3 is passed through a 180-mesh sieve to obtain the slurry below the sieve, i.e., the active slurry, and the residue above the sieve, and the residue above the sieve is used as construction waste-based regenerated sand;

[0065] The preparation process of the construction solid waste-based polymer gelling material comprises the following steps:

[0066] Step 1: According to the design requirements of the polymer cementitious material based on construction solid waste, the amount of active slurry and compensating agent are calculated respectively. The compensating agent is fly ash and gasified slag in a mass ratio of 1:1, and the mass ratio of active slurry to compensating agent is 1.1:1. The compensating agent is pre-treated by ball milling to a gradation of less than 180 mesh for standby use;

[0067] Step 2, weighing the active slurry according to the calculated amount in step 1, and pre-stirring it with a disperser for 30 seconds, then adding the compensating agent fly ash and gasified slag and continuing to stir for 10 minutes to prepare a construction solid waste-based polymer cementitious material; the construction solid waste-based polymer cementitious material is used to prepare a roadbed and pavement building material within 3 minutes after preparation, otherwise the construction solid waste-based polymer cementitious material is stirred again at a speed of 1800 rpm for 5 minutes before being used to prepare a roadbed and pavement building material;

[0068] The mass ratio of aggregate to construction solid waste-based polymer cementitious material used in the preparation process of the high-strength sleeper is 1.9:1, the gravel in the aggregate is a natural stone grading with particle sizes of 5mm-10mm and 10mm-20mm in a mass ratio of 3:7, the sand-gravel ratio is 0.5, and the standard sample after molding is cured for 7 days at a temperature of 20℃±2℃ and a humidity of not less than 95%. The compressive strength of the prepared high-strength sleeper can reach 60MPa.

[0069] After testing, the high-strength sleepers prepared in this embodiment meet the requirements of GB / T 37330-2019 "Concrete sleepers for ballasted track sleepers".

[0070] Example 2

[0071] The difference between this embodiment and Embodiment 1 is that the target product, the roadbed and pavement building material, is imitation stone bricks for roads, the compensating agent used in the preparation process of the construction solid waste base polymer cementitious material is gasified slag and furnace slag in a mass ratio of 3:1, and the mass ratio of the active slurry to the compensating agent is 1.2:1; the mass ratio of the aggregate used in the preparation process of the imitation stone bricks for roads to the construction solid waste base polymer cementitious material is 2.0:1, the gravel in the aggregate is a natural stone grading with a particle size of 3mm to 5mm, the sand and gravel ratio is 0.8, and the standard sample curing system after molding is natural curing.

[0072] According to tests, the imitation stone bricks for roads prepared in this embodiment have a compressive strength of not less than 40 MPa, and a flexural strength of not less than 4.0 MPa, which meet the requirements of GB / T 28635-2012 "Concrete Pavement Bricks".

[0073] Example 3

[0074] The difference between this embodiment and Embodiment 1 is that the target product, the roadbed and pavement building material, is a permeable road brick, the compensating agent used in the preparation process of the construction solid waste base polymer cementitious material is fly ash, and the mass ratio of the active slurry to the compensating agent is 1.2:1; the mass ratio of the aggregate used in the preparation process of the imitation stone bricks for roads to the construction solid waste base polymer cementitious material is 2.0:1, the gravel in the aggregate is a natural stone grading with a particle size of 8mm to 15mm, the sand and gravel ratio is 0.4, and the standard sample curing system after molding is natural curing.

[0075] After testing, the flexural strength of the road permeable brick prepared in this embodiment is not less than 3.0MPa, the splitting tensile strength is not less than 3.0MPa, and the water permeability coefficient is not less than 1.0×10 -2 cm / s, meeting the requirements of GB / T28635-2012 "Concrete Pavement Bricks".

[0076] Example 4

[0077] like Figure 1 As shown, in this embodiment, subway shield soil and construction waste soil with a mass ratio of 2:1 are used as construction solid waste raw materials to prepare construction solid waste-based polymer cementitious materials and construction waste-based regenerated sand, which are then mixed with aggregate and water through batching, mixing, molding, and curing to prepare high-strength sleepers;

[0078] The process for preparing the active slurry in the construction solid waste-based polymer cementitious material comprises the following steps:

[0079] Step 1: Raw material screening: The raw material construction solid waste is passed through a 1mm aperture sieve to obtain undersize material and oversize material, and the oversize material is used for construction waste-based regenerated sand;

[0080] Step 2, stirring: adding barium hydroxide, 6% hydrogen peroxide and sodium hydroxide as soluble stimulants in a mass ratio of 3:1:1 into water, stirring evenly and standing for more than 2 hours to obtain a pre-addition solution with a concentration of 200 g / L, and then mixing the undersize obtained in step 1 with the pre-addition solution and stirring with a high-speed disperser to obtain a preliminary slurry; the stirring speed is 3000 rpm, and the stirring time is 20 minutes;

[0081] Step 3, high-pressure activation: placing the prepared slurry obtained in step 2 in a reaction kettle for high-pressure activation to obtain an activated mixed slurry; the temperature of the high-pressure activation is 140° C., the pressure is 0.4 MPa, and the pressure holding time is 2 h;

[0082] Step 4, slurry-sand separation: the activated mixed slurry obtained in step 3 is passed through a 180-mesh sieve to obtain the slurry below the sieve, i.e., the active slurry, and the residue above the sieve, and the residue above the sieve is used as construction waste-based regenerated sand;

[0083] The preparation process of the construction solid waste-based polymer gelling material comprises the following steps:

[0084] Step 1: According to the design requirements of the polymer cementitious material based on construction solid waste, the amount of active slurry and compensating agent are calculated respectively, the compensating agent is fly ash, and the mass ratio of active slurry to compensating agent is 1.2:1, and the compensating agent is pre-treated by ball milling to a gradation of less than 180 mesh for standby use;

[0085] Step 2, weighing the active slurry according to the calculated amount in step 1, and pre-stirring it with a disperser for 30 seconds, then adding the compensating agent fly ash and gasified slag and continuing to stir for 10 minutes to prepare a construction solid waste-based polymer cementitious material; the construction solid waste-based polymer cementitious material is used to prepare a roadbed and pavement building material within 3 minutes after preparation, otherwise the construction solid waste-based polymer cementitious material is stirred again at a speed of 1800 rpm for 5 minutes before being used to prepare a roadbed and pavement building material;

[0086] The mass ratio of aggregate to construction solid waste-based polymer cementitious material used in the preparation process of the high-strength sleeper is 2.3:1, the gravel in the aggregate is a natural stone grading with particle sizes of 5mm-10mm and 10mm-20mm in a mass ratio of 3:7, the sand-gravel ratio is 0.5, and the standard sample after molding is cured for 7 days at a temperature of 20℃±2℃ and a humidity of not less than 95%. The compressive strength of the prepared high-strength sleeper can reach 60MPa.

[0087] After testing, the high-strength sleepers prepared in this embodiment meet the requirements of GB / T 37330-2019 "Concrete sleepers for ballasted track sleepers".

[0088] Example 5

[0089] The difference between this embodiment and Embodiment 4 is that the target product, the roadbed and pavement building material, is imitation stone bricks for roads, the compensating agent used in the preparation process of the construction solid waste base polymer cementitious material is gasified slag, and the mass ratio of the active slurry to the compensating agent is 1.3:1; the mass ratio of the aggregate used in the preparation process of the imitation stone bricks for roads to the construction solid waste base polymer cementitious material is 2.0:1, the gravel in the aggregate is a natural stone grading with a particle size of 3mm to 5mm, the sand and gravel ratio is 0.8, and the standard sample curing system after molding is natural curing.

[0090] According to tests, the imitation stone bricks for roads prepared in this embodiment have a compressive strength of not less than 40 MPa, and a flexural strength of not less than 4.0 MPa, which meet the requirements of GB / T 28635-2012 "Concrete Pavement Bricks".

[0091] Example 6

[0092] The difference between this embodiment and Embodiment 4 is that the target product, the roadbed and pavement building material, is a permeable road brick, the compensating agent used in the preparation process of the construction solid waste base polymer cementitious material is slag, and the mass ratio of the active slurry to the compensating agent is 1.4:1; the mass ratio of the aggregate used in the preparation process of the imitation stone bricks for roads to the construction solid waste base polymer cementitious material is 2.0:1, the gravel in the aggregate is a natural stone grading with a particle size of 8mm to 15mm, the sand and gravel ratio is 0.4, and the standard sample curing system after molding is natural curing.

[0093] After testing, the flexural strength of the road permeable brick prepared in this embodiment is not less than 3.0MPa, the splitting tensile strength is not less than 3.0MPa, and the water permeability coefficient is not less than 1.0×10 -2 cm / s, meeting the requirements of GB / T28635-2012 "Concrete Pavement Bricks".

[0094] Example 7

[0095] like Figure 1 As shown, in this embodiment, subway shield soil and construction waste soil with a mass ratio of 5:1 are used as construction solid waste raw materials to prepare construction solid waste-based polymer cementitious materials and construction waste-based regenerated sand, which are then mixed with aggregate and water through batching, mixing, molding, and curing to prepare high-strength rail sleepers;

[0096] The process for preparing the active slurry in the construction solid waste-based polymer cementitious material comprises the following steps:

[0097] Step 1: Raw material screening: The raw material construction solid waste is passed through a 1mm aperture sieve to obtain undersize material and oversize material, and the oversize material is used for construction waste-based regenerated sand;

[0098] Step 2, stirring: adding barium hydroxide in a mass ratio of 5:1:2, hydrogen peroxide with a mass concentration of 6%, and sodium hydroxide as soluble stimulants into water, stirring evenly, and standing for more than 2 hours to obtain a pre-addition solution with a concentration of 200 g / L, and then mixing the screened material obtained in step 1 with the pre-addition solution and stirring with a high-speed disperser to obtain a preliminary slurry; the stirring speed is 3000 rpm, and the stirring time is 20 minutes;

[0099] Step 3, high-pressure activation: placing the prepared slurry obtained in step 2 in a reaction kettle for high-pressure activation to obtain an activated mixed slurry; the high-pressure activation temperature is 150° C., the pressure is 0.5 MPa, and the pressure holding time is 2 h;

[0100] Step 4, slurry-sand separation: the activated mixed slurry obtained in step 3 is passed through a 180-mesh sieve to obtain the slurry below the sieve, i.e., the active slurry, and the residue above the sieve, and the residue above the sieve is used as construction waste-based regenerated sand;

[0101] The preparation process of the construction solid waste-based polymer gelling material comprises the following steps:

[0102] Step 1, according to the design requirements of the polymer cementitious material based on construction solid waste, the amount of active slurry and compensating agent are calculated respectively, the compensating agent is fly ash, gasified slag and slag in a mass ratio of 2:1:1, and the mass ratio of active slurry to compensating agent is 1.1:1, and the compensating agent is pre-treated by ball milling to a gradation of less than 180 mesh for standby use;

[0103] Step 2, weighing the active slurry according to the calculated amount in step 1, and pre-stirring it with a disperser for 30 seconds, then adding the compensating agent fly ash and gasified slag and continuing to stir for 10 minutes to prepare a construction solid waste-based polymer cementitious material; the construction solid waste-based polymer cementitious material is used to prepare a roadbed and pavement building material within 3 minutes after preparation, otherwise the construction solid waste-based polymer cementitious material is stirred again at a speed of 1800 rpm for 5 minutes before being used to prepare a roadbed and pavement building material;

[0104] The mass ratio of aggregate to construction solid waste-based polymer cementitious material used in the preparation process of the high-strength sleeper is 2.3:1, the gravel in the aggregate is a natural stone grading with particle sizes of 5mm-10mm and 10mm-20mm in a mass ratio of 3:7, the sand-gravel ratio is 0.5, and the standard sample after molding is cured for 7 days at a temperature of 20℃±2℃ and a humidity of not less than 95%. The compressive strength of the prepared high-strength sleeper can reach 60MPa.

[0105] After testing, the high-strength sleepers prepared in this embodiment meet the requirements of GB / T 37330-2019 "Concrete sleepers for ballasted track sleepers".

[0106] Example 8

[0107] The difference between this embodiment and Embodiment 7 is that the target product, the roadbed and pavement building material, is imitation stone bricks for roads, the compensating agent used in the preparation process of the construction solid waste base polymer cementitious material is fly ash, gasified slag and slag in a mass ratio of 2:1:1, and the mass ratio of the active slurry to the compensating agent is 1.2:1; the mass ratio of the aggregate used in the preparation process of the imitation stone bricks for roads to the construction solid waste base polymer cementitious material is 2.0:1, the gravel in the aggregate is a natural stone grading with a particle size of 3mm to 5mm, the sand and gravel ratio is 0.8, and the standard sample curing system after molding is natural curing.

[0108] According to tests, the imitation stone bricks for roads prepared in this embodiment have a compressive strength of not less than 40 MPa, and a flexural strength of not less than 4.0 MPa, which meet the requirements of GB / T 28635-2012 "Concrete Pavement Bricks".

[0109] Example 9

[0110] The difference between this embodiment and Embodiment 7 is that the target product, the roadbed and pavement building material, is a permeable road brick, the compensating agent used in the preparation process of the construction solid waste base polymer cementitious material is fly ash, gasified slag and slag in a mass ratio of 2:1:1, and the mass ratio of the active slurry to the compensating agent is 1.3:1; the mass ratio of the aggregate and the construction solid waste base polymer cementitious material used in the preparation process of the imitation stone bricks for roads is 2.0:1, the gravel in the aggregate is a natural stone grading with a particle size of 8mm to 15mm, the sand and gravel ratio is 0.4, and the standard sample curing system after molding is natural curing.

[0111] After testing, the flexural strength of the road permeable brick prepared in this embodiment is not less than 3.0MPa, the splitting tensile strength is not less than 3.0MPa, and the water permeability coefficient is not less than 1.0×10 -2 cm / s, meeting the requirements of GB / T28635-2012 "Concrete Pavement Bricks".

[0112] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing roadbed and pavement building materials from construction solid waste polymers, characterized in that: The construction solid waste-based polymer cementitious materials and construction waste-based regenerated sand, aggregates and water prepared with construction solid waste as raw materials are batched, mixed, molded and cured to prepare construction materials for roadbed and pavement; the construction materials for roadbed and pavement include high-strength sleepers, imitation stone bricks for roads and permeable bricks for roads; The construction solid waste-based polymer cementitious material is prepared by proportioning, mixing and stirring an active slurry and a compensating agent, wherein the soluble activator added to the active slurry is barium hydroxide and hydrogen peroxide, or barium hydroxide, hydrogen peroxide and sodium hydroxide, the compensating agent contains sodium, calcium and aluminum ions, and the compensating agent is prepared by one or more of gasified slag, fly ash and slag, and the mass content of Al2O3 in the compensating agent is greater than 15%, the mass content of CaO is greater than 10%, the mass content of Na2O is greater than 3%, and the grading is less than 180 meshes, wherein the preparation method of the active slurry comprises the following steps: Step 1: Raw material screening: The raw material construction solid waste is passed through a 1mm aperture sieve to obtain undersize material and oversize material, and the oversize material is used for construction waste-based regenerated sand; Step 2, stirring: adding a soluble stimulant into water, stirring evenly and then standing for more than 2 hours to obtain a pre-addition solution with a concentration of 200 g / L, then mixing the undersize obtained in step 1 with the pre-addition solution and stirring with a high-speed disperser to obtain a preliminary slurry; the stirring speed is 3000 rpm and the stirring time is 20 minutes; Step 3, high-pressure activation: placing the prepared slurry obtained in step 2 in a reaction kettle for high-pressure activation to obtain an activated mixed slurry; the temperature of the high-pressure activation is 120°C to 150°C, the pressure is 0.2MPa to 0.5MPa, and the pressure holding time is 2h; Step 4: Slurry-sand separation: The activated mixed slurry obtained in step 3 is passed through a 180-mesh sieve to obtain the slurry below the sieve, i.e., the active slurry, and the residue above the sieve, which is used as construction waste-based regenerated sand.

2. The method for preparing roadbed and pavement building materials from construction solid waste polymers according to claim 1, characterized in that: The raw materials for preparing the construction solid waste-based polymer cementitious material and the construction waste-based regenerated sand are derived from shield soil or construction waste in construction solid waste, and the mineral components in the preparation raw materials include muscovite, phlogopite, montmorillonite and quartz with a total mass content greater than 60%, and the mass content of SiO2 in the chemical composition of the preparation raw materials is greater than 50%, and the mass content of Al2O3 is not less than 15%.

3. The method for preparing roadbed and pavement building materials from construction solid waste polymer according to claim 1, characterized in that: The method for preparing a polymer gelling material based on construction solid waste by proportioning, mixing and stirring the active slurry and the compensating agent comprises the following steps: Step 1: According to the design requirements of the polymer cementitious material based on construction solid waste, the amount of active slurry and compensating agent are calculated respectively, and the mass ratio of active slurry to compensating agent is 1.1~1.4:1; Step 2. Weigh the active slurry according to the calculated amount in step 1, and pre-stir it for 30 seconds using a disperser, then add a compensating agent and continue stirring for 10 minutes to prepare a construction solid waste base polymer cementitious material; the construction solid waste base polymer cementitious material is used to prepare roadbed and pavement building materials within 3 minutes after preparation, otherwise the construction solid waste base polymer cementitious material must be stirred again at a speed of 1800 rpm for 5 minutes before being used to prepare roadbed and pavement building materials.

4. The method for preparing roadbed and pavement building materials from construction solid waste polymers according to claim 1, characterized in that: The mass ratio of the aggregate to the construction solid waste-based polymer cementitious material is 1.9-2.3:1; When the roadbed and pavement construction material is a high-strength rail sleeper, the gravel in the aggregate is a natural stone gradation composed of particle sizes of 5mm~10mm and 10mm~20mm in a mass ratio of 3:7, the sand-gravel ratio is 0.5, and the supplementer used in preparing the construction solid waste base polymer cementitious material is fly ash; When the roadbed and pavement construction material is imitation stone bricks for roads, the gravel in the aggregate is a natural stone gradation with a particle size of 3 mm to 5 mm, the sand-gravel ratio is 0.8, the supplementer used in preparing the construction solid waste base polymer cementitious material is gasified slag, and the maintenance system for preparing the imitation stone bricks for roads is natural maintenance; When the construction material for the roadbed and pavement is permeable road bricks, the gravel in the aggregate is a natural stone grading with a particle size of 8mm~15mm, the sand and gravel ratio is 0.4, the supplementer used to prepare the construction solid waste base polymer cementitious material is slag, and the maintenance system for preparing permeable road bricks is natural maintenance.

Citation Information

Patent Citations

  • Ecological precast concrete mixture

    CN105948596A

  • Alkali-activated slag geopolymer concrete and preparing method thereof

    CN106082927A